2022
DOI: 10.2147/opth.s368972
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Encourages Patients with Diabetes in Racial and Ethnic Minority Groups to Return for in-Person Ophthalmic Care During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic had a disproportionate impact on patients from racial and/or ethnic minority groups, causing many to delay healthcare. This study evaluates the role telehealth visits played in helping patients with diabetes mellitus (DM) return for subsequent, in-person eye examinations after the outbreak of COVID-19. Methods: This retrospective, cross-sectional study analyzed 8147 patients with DM who had completed an outpatient ophthalmology and/or optometry visit in 2019 and who were due for return ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…This study indicates that high FQHC-level telehealth use was associated with more sustained engagement in care for patients with diabetes at FQHCs in Massachusetts, with mixed effects on quality of care measures. Telehealth availability likely helped to partially mitigate the overall decrease in visit rates during COVID-19 by improving care access, while telehealth visits may have also provided the opportunity to encourage patients to return for in-person retinal screenings [7]. In contrast, decreases in measured blood pressure control may have resulted from the lack of standardized blood pressure documentation in EHRs during telehealth visits rather than poor control, although this was untestable in our data.…”
Section: Discussionmentioning
confidence: 73%
“…This study indicates that high FQHC-level telehealth use was associated with more sustained engagement in care for patients with diabetes at FQHCs in Massachusetts, with mixed effects on quality of care measures. Telehealth availability likely helped to partially mitigate the overall decrease in visit rates during COVID-19 by improving care access, while telehealth visits may have also provided the opportunity to encourage patients to return for in-person retinal screenings [7]. In contrast, decreases in measured blood pressure control may have resulted from the lack of standardized blood pressure documentation in EHRs during telehealth visits rather than poor control, although this was untestable in our data.…”
Section: Discussionmentioning
confidence: 73%
“…Future studies should address these gaps because it is known from studies that examined patients who identified as members of racial or ethnic minority groups in the USA that they face a disproportionately high burden from DR[ 1 2 ] and at the same time are less likely to access eye care. [ 35 ] Another limitation is that we used two FFA systems, which differ in contrast, resolution, and other machine-based variables; however, our study lacks the power to evaluate these differences. The platform-independent nature of our image alignment method likely moderates some of the impact from these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that certain demographic factors, such as sex and diabetes control, can influence the likelihood of male patients seeking in-person ophthalmology services, including during the COVID-19 pandemic [ 46 ]. Our study found that patients who received TRI were more likely to be male.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of only those patients who had completed a primary care visit within the study period, which spans the COVID-19 pandemic, also fails to capture patients who may have been disconnected from the healthcare system. Notably, such patients face not only poorer DM control but also an increased risk of developing DR [ 44 , 46 ]. Our electronic medical record-based study also misses the outcomes of eye care visits that occurred outside of our health system and were not reported back to a PCP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation